Recognizing the classroom environment as a dynamic contributor to physical health, cognitive abilities, and social well-being - Ashfaq Ahmad; Wajid Ali Ansari; Fatima Al-Kubaisi (Integration of Mankind and Society, 2026)
This study explores how human-centered environmental design affects students' general well-being, cognitive function, and health in learning environments. It examines how physical and sensory surroundings impact students' and teachers' health by influencing bodily functions, mental states, and social relationships. It does this by drawing on data from environmental psychology, ergonomics, and user experience design. The findings reveal that spaces integrating natural elements with adjustable ergonomic design and providing accessible areas for everyone create optimal conditions that enhance attention, reduce stress, and promote better overall health. The study highlights significant gaps in research focusing on long-term monitoring of subjects exposed to various sensory stimuli in real-world settings. It emphasizes the need for collaboration across multiple disciplines in educational space design to develop learning environments that foster student cognitive development and safeguard their health and well-being.